Recovery of the ciliated epithelium following acute bronchiolitis in infancy. Issue 7 (1st July 2005) - Wong, J Y W; Rutman, A; O'Callaghan, C
Abstract : Background: Little is known about the longitudinal changes in the ciliated respiratory epithelium of infants following viral bronchiolitis. A study was undertaken to investigate the time required for the ciliated epithelium to return to normal following bronchiolitis in infants treated with inhaled steroids or placebo. Methods: Thirty one previously healthy term infants were studied as part of a clinical trial to determine the effect of 12 weeks of treatment with inhaled fluticasone (FP) or placebo via a spacer device (17 FP, 14 placebo). Nineteen healthy children aged 0–6 years previously studied in our department were used as controls. Nasal biopsy specimens were taken from infants with bronchiolitis and ciliary beat frequency (CBF) was measured before treatment and repeated 3, 6, 12, and 24 weeks later. The epithelial ultrastructure was examined by transmission electron microscopy and a normal errors mixed model based on normal controls was used to examine the time for cilia to return to normal in bronchiolitic infants. Results: The mean CBF of infants with bronchiolitis (in Hz) at weeks 0, 3, 6, 12, and 24 were 0.5 (n = 4), 10.9 (n = 4), 12.0 (n = 9), 11.9 (n = 8), and 12.1 (n = 7) in the placebo group and 10.6 (n = 6), 11.4 (n = 9), 8.8 (n = 8), 10.9 (n = 4), and 13.2 (n = 7) in the FP group. The time for the epithelial ultrastructure to normalise was as follows: epithelial integrity score (13.1 weeks), % ciliated cells with loss of cilia (14.0 weeks), and % epithelial cells with abnormalities in projection (16.7 weeks) or mitochondria (15.9 weeks). Inhaled steroids had no significant effects on CBF or epithelial ultrastructure. Conclusion: Ciliary loss and epithelial abnormalities persist on average for 13–17 weeks following acute bronchiolitis in infancy.